2013
DOI: 10.4103/0300-1652.108886
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid profile in alcoholic cirrhosis: A study in a teaching hospital of north-eastern India

Abstract: Background:Alcoholic cirrhosis is often associated with impaired lipid metabolism. However, there are only a few studies regarding lipid profile in alcoholic cirrhosis that have been undertaken in India. The aim of the study is to assess the degree of alteration of serum lipid profile in alcoholic cirrhotic patients and also to detect its relationship with the age of the patients and the alcohol consumption pattern.Patients and Methods:This cross-sectional study was conducted in a teaching hospital of north-ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…The age differences between each demographic region are likely due to the care setting from which data were collected (population vs hospital-based), age structure of the population itself, and patterns of alcohol consumption. In fact, there were no differences in the mean age of hospitalized ALD patients in each geographic location 48–50 .…”
Section: Factors Associated With Aldmentioning
confidence: 86%
“…The age differences between each demographic region are likely due to the care setting from which data were collected (population vs hospital-based), age structure of the population itself, and patterns of alcohol consumption. In fact, there were no differences in the mean age of hospitalized ALD patients in each geographic location 48–50 .…”
Section: Factors Associated With Aldmentioning
confidence: 86%
“…Imbalance in serum lipoprotein can be due to cirrhosis of the liver, where cholesterol of low-density lipoprotein (LDL) variant and high-density lipoprotein (HDL) variant are reduced [ 5 ]. Dyslipidemia reported in patients of CLD is remarkable in contrast with other causes of secondary dyslipidemia as the composition, appearance, serum levels, and mobility of lipoproteins is disturbed [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, some studies showed a decrease in triglyceride in cirrhosis[ 36 ]. Liver biosynthesis is reduced with the progression of cirrhosis[ 37 ]. Although there were mixed findings of the relationship between cholesterol values and cirrhosis, our findings are compatible with the abovementioned relationship.…”
Section: Discussionmentioning
confidence: 99%